2020
DOI: 10.1186/s12929-020-00632-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of epithelial-mesenchymal transition: focusing on hypoxia and TGF-β signaling

Abstract: Epithelial-mesenchymal transition (EMT) is an important process triggered during cancer metastasis. Regulation of EMT is mostly initiated by outside signalling, including TGF-β, growth factors, Notch ligand, Wnt, and hypoxia. Many signalling pathways have been delineated to explain the molecular mechanisms of EMT. In this review, we will focus on the epigenetic regulation of two critical EMT signalling pathways: hypoxia and TGF-β. For hypoxia, hypoxia-induced EMT is mediated by the interplay between chromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 64 publications
2
112
0
Order By: Relevance
“…The complexes translocate into the nucleus, and regulate EMT target genes through interacting with various transcription factors [30]. Smad2/3, an intracellular signaling molecule, activates different EMT transcription factors [31]. In the present study, we found that the protein level of P-Smad2/3 was inhibited by HCK knockdown in GBM cells, suggesting HCK is involved in EMT via TGFβ/Smad signaling pathway.…”
Section: Discussionsupporting
confidence: 55%
“…The complexes translocate into the nucleus, and regulate EMT target genes through interacting with various transcription factors [30]. Smad2/3, an intracellular signaling molecule, activates different EMT transcription factors [31]. In the present study, we found that the protein level of P-Smad2/3 was inhibited by HCK knockdown in GBM cells, suggesting HCK is involved in EMT via TGFβ/Smad signaling pathway.…”
Section: Discussionsupporting
confidence: 55%
“…Small changes may lead to major consequences and result in cellular dysfunction or malignant outgrowth (Sun and Fang, 2016). Growing evidence suggests the epigenetic regulation of pro-inflammatory and pro-fibrotic gene expression, mediated by DNA methylation, histone modifications or microRNAs, is important in EMT and renal fibrogenesis (Wing et al, 2013;Rodriguez-Romo et al, 2015;Wanner and Bechtel-Walz, 2017;Lin and Wu, 2020).…”
Section: Epigenetic Regulation Of Pemt In the Kidneymentioning
confidence: 99%
“…Gene amplification/deletion/mutation or chromosomal translocation is abnormal genetic changes that lead to tumorigenesis and tumor development [5,6]. Recently, there has been increasing evidence that epigenetic regulation plays a major role in cancer [7,8]. Epigenetic modifications are heritable and reversible and can regulate gene expression and cancer progression without DNA sequence changes [1,5].…”
Section: Introductionmentioning
confidence: 99%